Presentation of an Organizational Ethics Model Based on Society 5.0 in Municipalities - Sabunchi, Tohid; Honarmand Azimi , Mortaza; Bohlooli, Nader (Future of Work and Digital Management Journal, 2026)
In the digital age and the technological transformations of Society 5.0, municipalities, as key institutions in urban governance, face new challenges in organizational ethics. This study was conducted with the aim of presenting an organizational ethics model based on Society 5.0 in the municipalities of West Azerbaijan, East Azerbaijan, Ardabil, and Zanjan provinces. The research method was designed in a mixed (qualitative–quantitative) form. In the qualitative section, based on the results obtained from the meta-synthesis approach and the systematic review of the existing literature, the dimensions and components of organizational ethics grounded in the requirements of Society 5.0 were identified. Then, the findings were screened and validated using experts’ opinions through the fuzzy Delphi method. To analyze causal relationships and prioritize the dimensions, the combined DEMATEL-ANP (DANP) model was applied. The DEMATEL method was used to distinguish cause (influential) and effect (influenced) dimensions, while the ANP (Analytic Network Process) method was used to assign weights and prioritize the criteria, and the conceptual model was presented. Data were collected through questionnaires with input from seven experts in the fields of urban management, organizational ethics, and Society 5.0, and analyzed using MATLAB and Excel software. The findings showed that criteria such as ethical leadership, corporate social responsibility, and social justice have the highest importance within the framework of organizational ethics in municipalities. Moreover, dimensions such as governance and ethics-oriented digital innovation, as well as workplace ethics and organizational culture, were identified as causal influencing factors, whereas dimensions such as citizen participation and inter-organizational cooperation were categorized as effect factors. The results of the study provide a systematic framework for understanding the interactions and hierarchies of organizational ethics dimensions in the context of the smart society and can serve as a scientific–practical basis for policymaking, planning, and improving the performance of municipalities in the path toward sustainable and human-centered development in Society 5.0.